Implementasi Model Quantum Teaching Dalam Meningkatkan Pemahaman Belajar Siswa pada Mata Pelajaran Al-Quran Hadis Kelas VII MTs Swasta Teladan Gebang - Maulida Maulida (Fakultas Syariah IAIN Laa Roiba Bogor, 2019)
The purpose of this study: To determine the application of the Quantum Teaching model in learning activities in the field of study of Al-Qur'an Hadith in MTs. Personal Exemplary Gebang. To determine the ability of students' understanding of learning the field of study of the Qur'an and Hadith in MTs. Personal Exemplary Gebang. To find out the application of the Quantum Teaching model in an effort to improve students' understanding of learning the field of study of the Qur'an and Hadith in MTs. Personal Exemplary Gebang. This research is a descriptive qualitative research, namely the data collected in the form of words and descriptions. According to Lexy J Moleong that